Desenho como linguagem: uma investigação nos livros didáticos de Osvaldo Sangiorgi – 1960 a 1980 - Conceição , Jucineide dos Santos (2017)
This study, through a historical perspective, proposes to respond to the concerns that arose from my pedagogical practice, as a mathematics teacher in the public network, and to contri-bute to the History of Education, especially for the teaching of Drawing and Mathematics in the secondary or 1st grade Brazilian course (currently called Primary Education II, corresponding to the 6th, 7th, 8th and 9th years). Our object of study is Drawing - Mathematics relationship, which went from drawing language, means of communication, expression of ideas, perception and representation of the real and abstract, to mere visualization of the abstract foundations of mathematics and illustrative drawing of the concepts of this discipline. The general objective was to investigate the role of drawing in Mathematics teaching through the analysis of the textbooks of Osvaldo Sangiorgi, published in the light of the Movement of Modern Mathematics (MMM), and attempted to answer the following question: how was drawing adopted by Osvaldo Sangiorgi in his compendia of Mathematics? To this end, the study adopted textbooks as an important instrument of Material School Culture and took all four volumes of Mathematics from the collections Mathematics Course and Modern Mathematics Course as sources of research and empirical basis, for presenting, respectively, the previous proposals and resulting from the MMM. The study of interdisciplinarity between the field of knowledge of Design, Education and Mathematics presented here is analyzed based on the history of the MMM, public policies for Education and for the organization of textbooks of Drawing and Mathematics in Brazil, created by the government agencies from 1960 to 1980, our temporal cut, trying to identify the changes that occurred in the teaching of Design and its relation with Mathematics in the face of the MMM's influence.